(untitled) (Revista Paradigma, 2020)
Starting from the analysis of the historical transformations of constitutionalism in the Modern State, and with the objective of demonstrating the role of the constitutional principle of access to justice in the guarantee of rights in the context of contemporary constitutionalism, marked by the growing judicialization of social relations, work will follow the deductive method of research, based on the doctrinal study on the subject. In the development of the problem, it will be pointed out that the judicialization is a fact, independent of the Judiciary, but results from the combination of several political-social-legal phenomena, in this context, it is urgent to ask how to situate the jurisdictional provision in this scenario? Thus, the importance of analyzing the constitutional principle of access to justice and its role in the realization of social rights, as well as the importance of expanding the concept of access to justice as an access to the just legal order arises.